2023
DOI: 10.1177/0271678x231182244
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous congestion alters brain metabolite profiles, impairing cognitive function

Abstract: Vascular cognitive impairment (VCI) represents the second most common cause of dementia after Alzheimer's disease, and pathological changes in cerebral vascular structure and function are pivotal causes of VCI. Cognitive impairment caused by arterial ischemia has been extensively studied the whole time; the influence of cerebral venous congestion on cognitive impairment draws doctors’ attention in recent clinical practice, but the underlying neuropathophysiological alterations are not completely understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…After the successful establishment of a validated rat model of cerebral venous congestion by JVL [ 5 , 6 , 16 , 17 ], behavioral tests were assessed before surgery as well as 7 days/14 days/1 month/3 months postoperatively (Fig. 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the successful establishment of a validated rat model of cerebral venous congestion by JVL [ 5 , 6 , 16 , 17 ], behavioral tests were assessed before surgery as well as 7 days/14 days/1 month/3 months postoperatively (Fig. 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…When confronted with continuous damage, similar to other systems in the organism, the function of the cerebrovascular system becomes decompensated, ultimately leading to increased energy requirements and further dysregulation of neurovascular and neurometabolic coupling function. Our previous studies have revealed that cerebral venous congestion can provoke brain metabolite profile alterations in response to CBF change and cerebral hypoperfusion [ 16 ]. Accordingly, we speculate that after transient ischemia and hypoxia in the brain, neurons are capable of making homeostatic changes to sustain their steady state and maintain the normal features of the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cerebral venous stenosis and thrombosis can also result in an alteration of VTT and have been suggested to increase the risk of hemorrhagic conversion in stroke patients 24,25 . Cerebral venous congestion has also been suggested to impair cognitive function 26 . The measurement of VTT, therefore, opens several research avenues in understanding vascular function in the normal and pathological brain.…”
Section: Introductionmentioning
confidence: 99%